All Saint's Church, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2010)
Image depicts a view of the All Saint's Church, located in the capital city of Port of Spain, Trinidad, while Trinidad was still a British colony.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Anglican church buildings--Trinidad and Tobago; Church buildings--Trinidad and Tobago